Flexibilisierung und Persuasion - Rocco, Goranka (Linguistik Online, 2019)
The article illustrates and compares some of the persuasive strategies of the political and entrepreneurial discourse on labour market flexibilization in different contexts: within the political discourse on labour market reforms and on socio-democratic/leftist basic values, and within the entrepreneurial communication and self-presentation (job advertisements, annual relations, personnel manager guides).